Kesalahan Fonologi dalam Pembelajaran Muhadatsah - Afdiantari Makalunsenge; Zohra Yasin; Muhammad Nur Iman; Asfar Rinaldy (Al-Kilmah: Jurnal Pendidikan Bahasa Arab dan Humaniora, 2022)
This study is motivated by frequent phonological errors made by ninth-grade students at MTs Al-Falah Limboto Barat in pronouncing Arabic sentences, particularly in muhadatsah (conversational practice). The study aims to analyze the phonological errors that occur and the factors influencing them. The method employed is descriptive quantitative, with the research population comprising all ninth-grade students. Data were collected through observations, online interviews, documentation, and oral tests. The findings indicate that phonological errors predominantly occur in the pronunciation of similar-sounding letters, such as the pronunciation of the letter (د) as (ت). The primary contributing factors include a lack of interest in learning, insufficient focus, and unengaging learning materials. The implication of this research is the necessity for enhancing the quality of Arabic language instruction and more intensive practice in phonological learning. In conclusion, phonological errors can be minimized through more effective teaching strategies.